Synthesis of Ni–Co-Fe layered double hydroxide and Fe2O3/Graphene nanocomposites as actively materials for high electrochemical performance supercapacitors. (10th September 2019) - Pourfarzad, Hamed; Shabani-Nooshabadi, Mehdi; Ganjali, Mohammad Reza; Kashani, Hamideh
Abstract: Supercapacitors, as a fresh class of electrochemical energy storage devices are currently of widespread interest in energy storage, which has become a research area due to outstanding performance features such as high lifetime, high power density, high safety, and low maintenance costs. In this study, we synthesize Co, Ni and Fe layered double hydroxides (NiCoFe–LDHs) on Nickel–foam as novel positive electrode and Fe2 O3 /Graphene as novel negative electrode for supercapacitve energy storage application. The electrochemical efficiencies of NiCoFe–LDHs have been explored and optimized by changing the amounts of Ni, Co and Fe via electrochemical method. The NiCoFe–LDH sample with Ni:Co:Fe ratio of 2:1:1 has the maximum specific capacity, that is related to the synergistic effect of the presence of Co, Ni and Fe which causes increased conductivity, increased oxidation rate of insulators such as Ni(OH)2, increases the formation rate of Co IV active sites and facilitates the penetration of OH − and therefore accelerates the kinetic of process. NiCoFe-LDHs nanocomposite shows a significant and high specific capacitance of 3130 Fg -1 at a density of current of 1 Ag -1 . Furthermore, an asymmetric supercapacitor are created using NiCoFe-LDHs as the positive and the Fe2 O3 /Graphene as the negative electrode exhibits the maximum energy density of 101 Whkg −1 and the power density of 91.5 KWkg −1, as well as a long-term cycling stability (82.5% capacity retention after 5000 cycles).